Dicionários do GP 'Lexicologia e lexicografia contrastiva' - Xatara, Claudia Maria [UNESP] (2010)
This paper presents the results of our works, most special dictionaries of general language, mono, bi or multilingual, developed by researchers at five universities in Brazil and in collaboration with experts from three foreign universities.